High levels of histone acetylation modifications promote the formation of PGCs - Ziduo Zhao; Yuhui Wu; Fufu Cheng; Zhe Wang; Qingqing Geng; Yingjie Niu; Qisheng Zuo; Yani Zhang (Poultry Science)
This study investigates the role of histone acetylation in the differentiation of chicken embryonic stem cells (ESCs) into primordial germ cells (PGCs). Transcriptomic sequencing was used to analyze differentially expressed genes during this differentiation process, with functional annotation identifying genes associated with histone acetylation. To explore the role of acetylation, acetate and an acetyltransferase inhibitor (ANAC) were added to the ESCs induction medium. Transcriptomic analysis revealed that during ESCs differentiation into PGCs, genes involved in histone acetyltransferase activity were upregulated, while those associated with histone deacetylase activity were downregulated. Functional enrichment analysis indicated these genes are involved in pathways critical for germ cell differentiation, underscoring their importance in avian reproductive biology. Quantitative real-time PCR (qRT-PCR) confirmed significant differential expression of HAT8 and HDAC10 between ESCs and PGCs (P < 0.01). The acetate treatment group exhibited a significantly higher number of embryoid bodies and elevated expression levels of CVH, C-KIT, and NANOS3 compared to the ANAC group (P < 0.01). Furthermore, indirect immunofluorescence and flow cytometry demonstrated a significantly higher proportion of DDX4-positive cells in the acetate group (P < 0.01). These findings provide preliminary evidence that histone acetylation regulates chicken PGCs formation, offering a theoretical framework for the epigenetic induction of PGCs in vitro. This study enhances our understanding of the molecular mechanisms underlying PGCs development in poultry and contributes to advancements in avian reproductive technologies and genetic conservation.